Requirements for invasion of epithelial cells by Actinobacillus actinomycetemcomitans. - Sreenivasan, P K (1993)
Actinobacillus actinomycetemcomitans, an oral bacterium implicated in human periodontal disease, was recently demonstrated to invade cultured epithelial cells (D. H. Meyer, P. K. Sreenivasan, and P. M. Fives-Taylor, Infect. Immun. 59:2719-2726, 1991). This report characterizes the requirements for invasion of KB cells by A. actinomycetemcomitans. The roles of bacterial and host factors were investigated by using selective agents that influence specific bacterial or host cell functions. Inhibition of bacterial protein synthesis decreased invasion, suggesting the absence of a preformed pool of proteins involved in A. actinomycetemcomitans invasion. Inhibition of bacterial and eukaryotic energy synthesis also decreased invasion, confirming that A. actinomycetemcomitans invasion is an active process. Bacterial adherence to KB cells was indicated by scanning electron microscopy of infected KB cells. Further, the addition of A. actinomycetemcomitans-specific serum to the bacterial inoculum reduced invasion substantially, suggesting a role for bacterial attachment in invasion. Many of the adherent bacteria invaded the epithelial cells under optimal conditions. Inhibitors of receptor-mediated endocytosis inhibited invasion by A. actinomycetemcomitans. Like that of many facultatively intracellular bacteria, A. actinomycetemcomitans invasion was not affected by eukaryotic endosomal acidification. These are the first published observations describing the requirements for epithelial cell invasion by a periodontopathogen. They demonstrate that A. actinomycetemcomitans utilizes a mechanism similar to those used by many but not all invasive bacteria to gain entry into eukaryotic cells.